Pulmonary embolism in the elderly: a review on clinical, instrumental and laboratory presentation - Luca Masotti; Patrick Ray; Marc Righini; Gregoire Le Gal; Fabio Antonelli; et al (Vascular Health and Risk Management, 2008)
Luca Masotti1,8, Patrick Ray2, Marc Righini3, Gregoire Le Gal4, Fabio Antonelli5, Giancarlo Landini1, Roberto Cappelli6, Domenico Prisco7, Paola Rottoli81Internal Medicine, Cecina Hospital, Cecina, Italy; 2Department of Emergency Medicine, Centre Hospitalo-Universitaire Pitié-Salpêtrière, Université Pierre et Marie Curie-Paris 6, Paris, France; 3Division of Angiology and Hemostasis, Geneva University Hospital and Faculty of Medicine, Geneva, Switzerland; 4Department of Internal Medicine and Chest Diseases, Brest University Hospital, Brest, France; 5Clinical Chemistry, Cecina Hospital, Cecina, Italy; 6Department of Internal, Cardiovascular and Geriatric Medicine, University of Siena, Siena, Italy; 7Department of Critical Care Medicine, Thrombosis Centre, Careggi Hospital, Florence, Italy; 8Departiment of Clinical Medicine and Immunological Sciences, Division of Respiratory Diseases, University of Siena, Siena, ItalyObjective: Diagnosis of pulmonary embolism (PE) remains difficult and is often missed in the elderly due to nonspecific and atypical presentation. Diagnostic algorithms able to rule out PE and validated in young adult patients may have reduced applicability in elderly patients, which increases the number of diagnostic tools use and costs. The aim of the present study was to analyze the reported clinical presentation of PE in patients aged 65 and more.Materials and Methods: Prospective and retrospective English language studies dealing with the clinical, instrumental and laboratory aspects of PE in patients more than 65 and published after January 1987 and indexed in MEDLINE using keywords as pulmonary embolism, elderly, old, venous thromboembolism (VTE) in the title, abstract or text, were reviewed.Results: Dyspnea (range 59%–91.5%), tachypnea (46%–74%), tachycardia (29%–76%), and chest pain (26%–57%) represented the most common clinical symptoms and signs. Bed rest was the most frequent risk factor for VTE (15%–67%); deep vein thrombosis was detected in 15%–50% of cases. Sinus tachycardia, right bundle branch block, and ST-T abnormalities were the most frequent ECG findings. Abnormalities of chest X-ray varied (less than 50% in one-half of the studies and more than 70% in the other one-half). Arterial blood gas analysis revealed severe hypoxemia and mild hypocapnia as the main findings. D-Dimer was higher than cut-off in 100% of patients in 75% of studies. Clinical usefulness of D-Dimer measurement decreases with age, although the strategies based on D-Dimer seem to be cost-effective at least until 80 years.Conclusion: Despite limitations due to pooling data of heterogeneous studies, our review could contribute to the knowledge of the presentation of PE in the elderly with its diagnostic difficulties. A diagnostic strategy based on reviewed data is proposed.Keywords: pulmonary embolism, diagnosis, elderly, symptoms